PHYSICAL WEATHERING OF MARBLES CAUSED BY ANISOTROPIC THERMAL EXPANSION - Siegesmund S.; Ullemeyer K.; Weiss T.; Tschegg E.K. (My University, 2000)
Marbles as building stones as well as in their natural environments show complex weathering phenomena. The most important damage scenario is based on the highly anisotropic thermal expansion coefficient α of calcite, i.e. extreme expansion parallel and contraction normal to the crystallographic c-axis. Therefore, the rock fabric and especially the lattice-preferred orientation (texture) of calcite and/or dolomite as the predominant mineral phases in marbles have a significant influence on the mechanical weathering. The textures of marbles from five different locations vary from a more or less perfect prolate to moderate oblate shape of the [006] pole figure tensor. Accordingly, the texture-derived bulk thermal dilatation anisotropy covers a broad range from –0.048 to 0.680. The modelled thermal dilatations correlate with those obtained from experimental measurements. The difference in magnitude is basically explained by the microcrack fabrics which was not considered in the computations. All samples show a deterioration due to thermal treatment regardless of the strength of texture. The directional dependence of (a) the total magnitude of the thermal dilatation coefficient and (b) of the residual strain is highest in marbles with a strong texture, whereas the Carrara marble with a weak texture exhibits a uniform crack formation. The progressive loss of cohesion along grain boundaries due to dilatancy may serve as an example for the initial stage of physical weathering.